Evaluación del efecto del consumo de agua de bebida sobre el número de crías nacidas al parto en cuyes (Cavia porcellus), Ibarra – Imbabura - Quiroz Montenegro, Erika Daniela (2022)
Guinea pig farming is one of the most important activities within the families of the Ecuadorian highlands, however, the low profitability of the producers is reflected, by not meeting the demand for this species. One of the main causes of this problem is the low number of pups born at birth, showing the inadequate handling of the animals. A solution to this is the supply of drinking water in diets, allowing them to have better performance in terms of zootechnical parameters. The general objective of this study was to evaluate the effect of drinking water consumption on the number of young born alive at parturition in guinea pigs (Cavia porcellus). For the development of the research, two stages were considered, the performance of the water quality analysis in the chemistry laboratory of the Pontifical Catholic University of Ecuador, Ibarra Headquarters and the evaluation of the effect of drinking water consumption, carried out in the city of Ibarra, province of Imbabura. The research used a completely randomized design (DCA), using 36 animals, to which three different doses of drinking water were applied throughout the experimental phase\; After executing the respective breeding, the removal of males was carried out, in order to continue with the gestation of the females, to finally produce parturition and the evaluation of the productive and reproductive indices. The fruit of the research was evidenced through the data obtained for fertility, litter size and the average weights of breeders and offspring at birth and weaning. The study carried out shows that the consumption of drinking water ad libitum positively influences the number of young born alive at parturition, determining the increase in the litter and, therefore, the socioeconomic relevance that the proper management of this species entails.